Provably secure certificateless aggregate signature scheme in wireless roaming authentication - Zhi-yan XU; Li-bing WU; Li LI; De-biao HE (Tongxin xuebao)
Certificateless aggregate signature (CLAS) schemes have been widely applied in resource-constrained wireless mobile networks,because they could not only realize batch validation but also solve the certificate management and key escrow problems.It was shown that a certificateless aggregate signature in an anonymous roaming authentication scheme was vulnerable to the signature forge attack.To address the issue,a new secure and efficient certificateless aggregate signature scheme was presented,which required no bilinear pairing operations.And then the security of the scheme under the ECDLP assumption in the random oracle model was proved.Finally the performance of proposed scheme was evaluated.Compared with the original scheme,the proposal is more secure and the total computational cost is greatly reduced .